Anxiety Of Erun Gruwell In Freedom Writers Movie By Richard Lagravanese (2007): A Psychoanalytic Approach - SUPRIYANTI, WAHYU (2012)
The object of this research is the movie entitled Freedom Writers, by Richard LaGravenese. The study investigates how anxiety of the major character in Richard LaGravenese Freedom Writers specifically viewed from psychoanalytic approach. The research paper belongs to qualitative research. The object of study is Erin Gruwell in Freedom Writers movie. In this method, the writers use two data sources. The primary data source is the Freedom Writers movie itself, meanwhile the secondary one includes references and materials related to the study picking up from the books or internet. The methods used for collecting data are library research and documentation. The technique of data analysis is descriptive analysis. The result of the analysis shows that firstly, based on the structural analysis, it is clear that in this movie, and director wants to deliver a moral message that it requires a sense of danger in order to make an individual realize the reasonability of his or her own personality in social interaction. Secondly, the psychoanalytic analysis shows that anxiety develops out of a conflict between id, ego, and superego resulting in different types of anxieties.